2020
DOI: 10.1093/mnrasl/slaa149
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a hot ultramassive rapidly rotating DBA white dwarf

Abstract: We report the discovery of a nearby massive white dwarf with He-H atmosphere. The white dwarf is located at a distance of 74.5 ± 0.9 pc. Its radius, mass, effective temperature, H/He ratio and age are R = 2500 ± 100 km, M = 1.33 ± 0.01 $\rm M_{\odot }$, Teff = 31200 ± 1200 K, H/He ∼ 0.1 and 330 ± 40 Myr, respectively. The observed spectrum is redshifted by Vr = +240 ± 15 km s−1, which is mostly attributed to the gravitational redshift. The white dwarf shows a regular stable photometric variability with amplitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…The downward triangles mark when 10 % of the mass is solid while the upward triangles mark when 90% of the mass is solid. The large star shows ZTF J190132.9+145808.7 (Caiazzo et al 2021) and the small star shows WD J183202.83+085636.24 (Pshirkov et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The downward triangles mark when 10 % of the mass is solid while the upward triangles mark when 90% of the mass is solid. The large star shows ZTF J190132.9+145808.7 (Caiazzo et al 2021) and the small star shows WD J183202.83+085636.24 (Pshirkov et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…As our sample of nearby WDs becomes increasing complete, thanks in large part to Gaia (Gaia Collaboration et al 2018;Gentile Fusillo et al 2019), a significant number of white dwarfs with masses 1.3 M are being revealed and better described. These include longstudied objects like GD 50 (Bergeron et al 1991;Gagné et al 2018) and RE J0317-853 (Barstow et al 1995;Ferrario et al 1997;Külebi et al 2010) as well more recently characterized objects like WD J183202.83+085636.24 (Pshirkov et al 2020) and ZTF J190132.9+145808.7 (Caiazzo et al 2021). In their analysis of the 100 pc sample from the Montreal White Dwarf Database, Kilic et al (2021) identify 25 WDs with masses > 1.3 M (assuming H atmospheres and C/O cores).…”
mentioning
confidence: 99%
“…Ultra-massive H-deficient WDs are less frequent than H-rich objects, but at least a handful of them have been detected in the SDSS (Kleinman et al 2013;Reindl et al 2014;Koester et al 2020;Bédard et al 2020). In addition, an ultra-massive DB WD with an effective temperature well within the DBV instability strip has been detected by Richer et al (2019) in a young open cluster, and a hot rapidly rotating DBA WD with a stellar mass of 1.33 M has been discovered by Pshirkov et al (2020). By means of the analysis of the period-spacing and mode-trapping features, we have shown that the pulsational properties of the ultra-massive DB WDs are much more strongly dependent on their formation scenario than in the case of the DA WD ones studied in Althaus et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Its effective temperature, which is in excess of 25 000 K, places this ultra-massive DB WD inside the DBV instability strip. Recently, Pshirkov et al (2020) discovered an ultra-massive WD with He-rich atmosphere and traces of H (DBA spectral class) with T eff = 31 200 ± 1200 K and M = 1.33 M exhibiting photometric variability with a single period of 353.456 s, which could be due to fast rotation, supporting a merger scenario for its formation. However, it cannot be completely ruled out that the variability is due to pulsations since it is close to the blue edge of the DBV instability strip.…”
Section: Introductionmentioning
confidence: 96%
“…Advanced LIGO and the Einstein Tele-scope. If applying this GW emission model to a rotating WD and unless the quadrupole moments of WDs are much larger than ∼ 10 40 g cm 2 , we will get a much smaller GW amplitude 10 −30 because WDs have rotation periods 300 s (Pshirkov et al 2020;Reding et al 2020;Kawaler 2015;Kissin & Thompson 2015).…”
Section: Namementioning
confidence: 99%